Factors Affecting Price Spread Of Rice In Nepal - Shrestha, Rudra Bahadur (Journal of Agriculture and Environment, 2013)
Inefficient marketing service increases price spread, which is a common feature in developing countries. The study aimed to analyze factors affecting retail-price spread of rice in Nepal using the Relative Price Spread (RPS) model with cross section data collected from four districts namely Jhapa, Morang, Chitwan, and Rupandehi in 2008. The flow of the product was traced forward and backward from the selected wholesaler respondents for selecting the farmer and the retailor respondents randomly. The marketing margin is higher in the farm to wholesale market as compared to the wholesale to retail market. The result revealed that the marketing cost, wholesale price of rice, retail prices of rice, and market information to the farmer significantly influence the marketing margin. Reduction in the transportation cost, improving the market information system, and improving the role of farmer in price determination help reduce the marketing margin. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 47-52 DOI: http://dx.doi.org/10.3126/aej.v13i0.7587